2004
DOI: 10.4049/jimmunol.172.9.5287
|View full text |Cite
|
Sign up to set email alerts
|

Distinct IL-2 Receptor Signaling Pattern in CD4+CD25+ Regulatory T Cells

Abstract: Despite expression of the high-affinity IL-2R, CD4+CD25+ regulatory T cells (Tregs) are hypoproliferative upon IL-2R stimulation in vitro. However the mechanisms by which CD4+CD25+ T cells respond to IL-2 signals are undefined. In this report, we examine the cellular and molecular responses of CD4+CD25+ Tregs to IL-2. IL-2R stimulation results in a G1 cell cycle arrest, cellular enlargement and increased cellular survival of CD4+CD25+ T cells. We find a distinct pattern of IL-2R signaling in which the Janus ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
219
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(243 citation statements)
references
References 46 publications
18
219
1
5
Order By: Relevance
“…As previously reported, T reg died more quickly than T eff [12]. Furthermore, IL-2 rescued significantly more T reg than T eff from cell death, which reflects the well known dependency of highly purified CD4 + CD25 high cells on exogenous IL-2 in vitro [35,36]. Most importantly, we did not detect an increase of apoptotic or necrotic cell death in T reg from MS patients (spontaneous apoptosis 45.2 AE 7.5% (MS, n=8) vs. 45.7 AE 5.0% (controls, n=8) (Fig.…”
Section: T Reg From Ms Patients Do Not Display Enhanced Sensitivity Tsupporting
confidence: 80%
“…As previously reported, T reg died more quickly than T eff [12]. Furthermore, IL-2 rescued significantly more T reg than T eff from cell death, which reflects the well known dependency of highly purified CD4 + CD25 high cells on exogenous IL-2 in vitro [35,36]. Most importantly, we did not detect an increase of apoptotic or necrotic cell death in T reg from MS patients (spontaneous apoptosis 45.2 AE 7.5% (MS, n=8) vs. 45.7 AE 5.0% (controls, n=8) (Fig.…”
Section: T Reg From Ms Patients Do Not Display Enhanced Sensitivity Tsupporting
confidence: 80%
“…Interestingly, Bensinger et al [67] recently showed that peripheral Treg, stimulated in the presence of IL-2, show increased survival in the absence of Akt phosphorylation, suggesting that Akt activation is dispensable for Treg survival.…”
Section: Discussionmentioning
confidence: 99%
“…While knockout animal models have yielded contradictory results, in vitro signaling studies have indicated that IL-2R has different signaling properties in Treg when compared to conventional CD4 + T cells [33]. Specifically, IL-2R signaling activates STAT5, but not protein kinase B/Akt, due to the constitutive expression of phosphatidylinositol-phosphatase, phosphatase and tensin homolog deleted on chromosome 10 (PTEN).…”
Section: Discussionmentioning
confidence: 99%